Prescriptive Analytics Based Framework for Indian Stock Market Through a Detailed Study of Data Science Techniques - Aloorravi, Sulekha (Digital Repository of Theses, 2024)
This study will focus on developing a prescriptive framework that applies various techniques of data science, machine learning and deep learning to help individual investors understand market opportunities and make educated decisions in the Indian stock market. The study will review existing methodologies and research available in the field of Indian stock markets, identifying market opportunities and applying data science techniques. The study will rely on publicly available data sets related to stock prices and financial reports of individual firms. The study will find answers for research questions and will prescribe a framework for educated decision making in identifying market opportunities. Finally, the study will conclude the results. The study will also recommend further studies and identify limitations of the study.